Evaluation of PD-L1 Expression and HPV Genotyping in Anal Squamous Cell Carcinoma - Wessely, Anja; Heppt, Markus; Kammerbauer, Claudia; Steeb, Theresa; Kirchner, Thomas; Flaig, Michael J.; French, Lars E.; Berking, Carola; Schmoeckel, Elisa; Reinholz, Markus (Cancers, 2020)
Simple Summary
CRIS-Team WoS Importer:2020-11-06